Reduction of Charge Recombination by an Amorphous Titanium Oxide Interlayer in Layered Graphene/Quantum Dots Photochemical Cells - Yang, H.; Guo, C.; Guai, G.; Song, Q.; Jiang, San Ping; Li, C. (American Chemical Society, 2011)
The effect of an amorphous TiOx interlayer on layered graphene/quantum dots photochemical cells has been investigated. The addition of the TiOx interlayer eliminates the decay of photocurrent in the initial seconds after light illumination and significantly increases the slope of the steady-state photocurrent versus the light intensity. The open-circuit voltage decay measurements further illustrate a longer electron lifetime when an amorphous TiOx interlayer is applied. Consequently, the photocurrent and photovoltage of the photovoltaic cell with a TiOx interlayer are greatly increased. This work emonstrates that the graphene/amorphous TiOx composite structure effectively inhibits charge recombination while enhancing charge transfer, providing a promising scaffold for quantum dots and dye-sensitized photovoltaic cells.